2003
DOI: 10.1016/s0161-4754(03)00076-9
|View full text |Cite
|
Sign up to set email alerts
|

Spinal palpation: the challenges of information retrieval using available databases

Abstract: Methods:We formulated the following research question: "What is the reliability of spinal palpation procedures?" We identified specific Medical Subject Headings (MeSH) and key terms as used in osteopathic medicine, allopathic medicine, chiropractic, and physical therapy. Using PubMed, we formulated an initial search template and applied it to 12 additional selected databases. Subsequently we applied the inclusion criteria and evaluated the yield in terms of precision and sensitivity in identifying relevant stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 17 publications
3
17
0
Order By: Relevance
“…Our data reveal that scientists are aware of these indexing inadequacies and that they use a multiple-strategy approach to overcome existing retrieval limitations. This behavior has been reported in other studies as well (Murphy et al, 2003a(Murphy et al, , 2003b. The medical group used five search TABLE 2.…”
Section: Critical Taskssupporting
confidence: 77%
“…Our data reveal that scientists are aware of these indexing inadequacies and that they use a multiple-strategy approach to overcome existing retrieval limitations. This behavior has been reported in other studies as well (Murphy et al, 2003a(Murphy et al, , 2003b. The medical group used five search TABLE 2.…”
Section: Critical Taskssupporting
confidence: 77%
“…We were able to uncover an additional 29 articles using this process, which, when combined with those found in the database searches, is more than any other MP review to date. This experience was similar to that of Murphy et al, 94 who were still able to locate an additional 11 citations via manual searches and content experts, after searching 13 databases on the reliability of spinal palpation procedures.…”
Section: Discussionsupporting
confidence: 52%
“…This is strongly supported by a number of other studies [813, 15, 16, 1822, 33, 6678]. Studies evaluating this question within the musculoskeletal field make the same conclusion: searching more than one database is necessary [14, 17, 23, 32, 79–81]. Based on results from earlier studies and the results from the present study, recommendation for an optimal systematic literature search to locate RCTs within the musculoskeletal area may be to use the three generic databases: MEDLINE; EMBASE and CENTRAL, and an additional two or more other databases.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, when analysing the use of databases in Cochrane reviews, it was found that between 1 and 27 different databases was used [20], even though some studies indicates that searching no more than 3–5 databases seems to be sufficient,[8, 16, 17] and searching only one database would not be enough [19]. Even though MEDLINE, EMBASE and other major medical databases yield a high proportion of relevant studies, some studies found it necessary to include other sources such as reference- and citation search, browsing conference proceedings, asking experts and alike to identify all the relevant studies [9, 14, 17, 19]. The difference between the results from these studies could be due to their evaluation of different areas or due to the methods used to search the different databases; hence some of the above mentioned studies construct a new search strategy to identify studies in a given area thereby making the evaluation be dependent on not just the database, but also the quality/accuracy of the search strategy constructed [2123].…”
Section: Introductionmentioning
confidence: 99%